PENGARUH STRES KERJA, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KEINGINAN BERPINDAH KERJA (TURNOVER INTENTION) PADA KARYAWAN PT. ALAS WATU EMAS KABUPATEN KAMPAR - Deri Gusmanto; Marnis '; Marzolina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine effect of work stress, organizational culture and job satisfaction to turnover intentions employees PT.Alas Watu Gold District Kampar. The population in this study all employees of PT. Alas Watu Gold totaling 110. While the sampling technique with the formula proposed by Slovin order to obtain a sample sebayak 86 people. Analysis of data using multiple linear regression with SPSS version 18:00. Based on the results of data analysis known that the stress of work, organizational culture and job satisfaction simultaneously and partially significant effect to turnover intentions employees at PT.Alas Watu Gold District Kampar. The large number of such influence is 47.5% Based on the results of data analysis known that the stress of work, organizational culture and job satisfaction simultaneously and partially significant effect on the labor turnover intentions (turnover intention) to employees PT.Alas Watu Gold District Kampar. The large number of such influence is 47.5%. Companies should consider factors that affect employees' desire to come out with a way to handle the stress of employees, pay attention to the organizational culture and improve job satisfaction in the work that the employee's desire for the exit can be minimized. With that employees will feel heavy for leaving the company.Keyword : Stress, Organizational Culture, Job Satisfaction and Turnover Intentions.